2022
DOI: 10.3390/ma15217614
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of High Performance Concrete Mixed with Nano-Silica in Front of Sulfate Attack

Abstract: Nano-silica (NS) is an effective material to improve the strength and durability of high-performance concrete (HPC), but little information is available regarding its role in HPC response to long-term sulfate attack. In this study, six different dosages of NS (0%, 1%, 2%, 3%, 4%, and 5%) as cement partial replacement were mixed into HPC and the casted specimens were soaked in sulfate solution for different periods (0, 100, 200, and 300 days). The mass change, dynamic elastic modulus, compressive and splitting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 46 publications
2
7
0
Order By: Relevance
“…It also reduced the dimensions of the pores present and hence contributed to the reduction in permeability. Similar findings were reported by (Makwana et al, 2021;Nie et al, 2022;Thakkar et al, 2020). Mercury Intrusion Porosimetry (MIP) tests by (Ghafoori et al, 2020) showed that for mortars containing 6% Nano silica, the void volume proportion of gel pores and micropores increased in comparison with those of the control, and there was an overall reduction in the capillary macro pores.…”
Section: Porosity and Permeabilitysupporting
confidence: 74%
See 4 more Smart Citations
“…It also reduced the dimensions of the pores present and hence contributed to the reduction in permeability. Similar findings were reported by (Makwana et al, 2021;Nie et al, 2022;Thakkar et al, 2020). Mercury Intrusion Porosimetry (MIP) tests by (Ghafoori et al, 2020) showed that for mortars containing 6% Nano silica, the void volume proportion of gel pores and micropores increased in comparison with those of the control, and there was an overall reduction in the capillary macro pores.…”
Section: Porosity and Permeabilitysupporting
confidence: 74%
“…Addition of Nano silica was reported to increase the compressive strength of cement (Makwana et al, 2021;Moslemi et al, 2014;Nie et al, 2022;Thakkar et al, 2020;Wang et al, 2020) . Research (Rzepka & Kȩdzierski, 2020) found that early compressive strength amounting to 3.5 MPa was achieved by slurries after times between approximately 7 h and 14 h. After 28 days of hydration, the compressive strength of the hardened cement stones had very high values up to 50 MPa (Rzepka & Kȩdzierski, 2020).…”
Section: Compressive Strengthmentioning
confidence: 99%
See 3 more Smart Citations